Unraveling the influence of TTF-1 expression on immunotherapy outcomes in PD-L1-high non-squamous NSCLC: a retrospective multicenter study - Nishioka, Naoya; Kawachi, Hayato; Yamada, Tadaaki; Tamiya, Motohiro; Negi, Yoshiki; Goto, Yasuhiro; Nakao, Akira; Shiotsu, Shinsuke; Tanimura, Keiko; Takeda, Takayuki; Okada, Asuka; Harada, Taishi; et al. (Frontiers in Immunology, 2024)
Introduction Several studies explored the association between thyroid transcription factor-1 (TTF-1) and the therapeutic efficacy of immunotherapy. However, the effect of TTF-1 on the therapeutic efficacy of programmed death-1 (PD-1) inhibitor/chemoimmunotherapy in patients with non-squamous non-small cell lung cancer (non-Sq NSCLC) with a programmed death-ligand 1 (PD-L1) tumor proportion score of 50% or more who are highly susceptible to immunotherapy remains unresolved. Therefore, we evaluated whether TTF-1 has a clinical impact on this population. Methods Patients with non-Sq NSCLC and high PD-L1 expression who received PD-1 inhibitor monotherapy or chemoimmunotherapy between May 2017 and December 2020 were retrospectively enrolled. Treatment efficacy was compared after adjusting for baseline differences using propensity score matching. Results Among the 446 patients with NSCLC with high PD-L1 expression, 266 patients with non-Sq NSCLC were analyzed. No significant differences in therapeutic efficacy were observed between the TTF-1-positive and -negative groups in the overall and propensity score-matched populations. Of chemoimmunotherapy, pemetrexed containing regimen significantly prolonged progression-free survival compared to chemoimmunotherapy without pemetrexed, regardless of TTF-1 expression (TTF1 positive; HR: 0.46 (95% Confidence interval: 0.26-0.81), p<0.01, TTF-1 negative; HR: 0.29 (95% Confidence interval: 0.09-0.93), p=0.02). Discussion TTF-1 expression did not affect the efficacy of PD-1 inhibitor monotherapy or chemoimmunotherapy in patients with non-Sq NSCLC with high PD-L1 expression. In this population, pemetrexed-containing chemoimmunotherapy demonstrated superior anti-tumor efficacy, irrespective of TTF-1 expression.